Answer:
D) 2
The average rate of change of f(x)
A(x) =2
Explanation:
Step(i):-
Given that the function f(x) = x² - 3x -10
Given x =a = -5 and y = b = 10
The average rate of change of f(x)
![A(x) = (f(b)-f(a))/(b-a)](https://img.qammunity.org/2022/formulas/mathematics/college/ms2xks65nfps1vlrc6v87b3c89sqsblv3v.png)
Step(ii):-
f(x) = x² - 3x -10
f(-5) = (-5)² - 3(-5) -10 = 25+15-10=30
f(10) = (10)² -3(10)-10 = 100 -30 -10 =60
The average rate of change of f(x)
![A(x) = (f(b)-f(a))/(b-a)](https://img.qammunity.org/2022/formulas/mathematics/college/ms2xks65nfps1vlrc6v87b3c89sqsblv3v.png)
![A(x) = (60-30)/(10-(-5))= (30)/(15) = 2](https://img.qammunity.org/2022/formulas/mathematics/high-school/jo8a2o05y2mqpgro74src1jmmpoms3pn8v.png)
A(x) =2